Cannabis use as a factor of lower corpulence in hepatitis C-infected patients: results from the ANRS CO22 Hepather cohort - Tangui Barré; Fabrice Carrat; Clémence Ramier; Hélène Fontaine; Vincent Di Beo; Morgane Bureau; Céline Dorival; Dominique Larrey; Elisabeth Delarocque-Astagneau; Philippe Mathurin; Fabienne Marcellin; Ventzislava Petrov-Sanchez; et al. (BMC, 2022)
Abstract Background Patients with chronic hepatitis C virus (HCV) infection are at greater risk of developing metabolic disorders. Obesity is a major risk factor for these disorders, and therefore, managing body weight is crucial. Cannabis use, which is common in these patients, has been associated with lower corpulence in various populations. However, this relationship has not yet been studied in persons with chronic HCV infection. Methods Using baseline data from the French ANRS CO22 Hepather cohort, we used binary logistic and multinomial logistic regression models to test for an inverse relationship between cannabis use (former/current) and (i) central obesity (i.e., large waist circumference) and (ii) overweight and obesity (i.e., elevated body mass index (BMI)) in patients from the cohort who had chronic HCV infection. We also tested for relationships between cannabis use and both waist circumference and BMI as continuous variables, using linear regression models. Results Among the 6348 participants in the study population, 55% had central obesity, 13.7% had obesity according to their BMI, and 12.4% were current cannabis users. After multivariable adjustment, current cannabis use was associated with lower risk of central obesity (adjusted odds ratio, aOR [95% confidence interval, CI]: 0.45 [0.37-0.55]), BMI-based obesity (adjusted relative risk ratio (aRRR) [95% CI]: 0.27 [0.19-0.39]), and overweight (aRRR [95% CI]: 0.47 [0.38-0.59]). This was also true for former use, but to a lesser extent. Former and current cannabis use were inversely associated with waist circumference and BMI. Conclusions We found that former and, to a greater extent, current cannabis use were consistently associated with smaller waist circumference, lower BMI, and lower risks of overweight, obesity, and central obesity in patients with chronic HCV infection. Longitudinal studies are needed to confirm these relationships and to assess the effect of cannabis use on corpulence and liver outcomes after HCV cure. Trial registration ClinicalTrials.gov identifier: NCT01953458 .